An integrative review on physical restraint in adult critical care unit - Kavumpurath, Janisha; KC Mani, Kulanthayan; Refaat, Fatma; Devaraj, Navin; Abdul Rashid, Aneesa; Ibrahim, Noor Airini (F1000Research, 2022)
Background: Physical restraints (PRs) are frequently used in adult critical care units to protect staff and prevent self-harm, despite the fact that they represent significant safety risks. Restraint complications may have an impact on the patient's long- and short-term outcomes. This study aims to examine the recent evidence on the use of PR in adult critical care. Method: This integrative review included the studies published between January 2009 and December 2019 and the literature search was conducted in July 2020. The databases searched included EBSCOhost, Ovid, ProQuest, PubMed, Wiley Online Library, SCOPUS, and ScienceDirect. The keywords included in the search were restraint, critical care, intensive care, ICU, mechanical ventilation, intubation, nursing, and experience. A checklist based on the CASP checklist and the JBI Critical Appraisal Tool was used to assess the methodological quality. Results: The findings were evaluated and summarized into seven key topics after twenty-one publications were found to be evaluated. i) High prevalence of PR application in adult critical care unit; ii) determinants of PR applications; iii) types of PR in adult critical care units; iv) decision maker of PR; v) moral and ethical dilemma in PR application; vi) awareness and guidelines for PR applications; vii) common complications and use of sedation, analgesics, antipsychotic drugs in PR application. Conclusion: The number of days PR is used is related to the risk of an adverse event. In order to standardize nursing practice, ICU nurses require greater training on the ideas of PR use. Evidence-based recommendations will assist critical care nurses in making the best judgments possible concerning the use of PR.